Regulation by Reputation? Intermediaries, Labor Abuses, and International Migration - Fernando, A. Nilesh; Singh, Niharika (The Review of Economics and Statistics, 2025)
Abstract Migrant workers and employers rely on intermediaries to facilitate labor market placements. If information frictions obscure their reputation, however, intermediaries may under-invest in placement quality. Using data on over 1.5 million Sri Lankan migrants to the Gulf region, we examine the effects of a government-run intermediary rating program that publicly revealed ratings two years after it was announced. Prior to the ratings' public release, under-performing intermediaries invest in the rating criteria and place migrants in less abusive and more remunerative employment. Our results suggest the government's threat of quality revelation induced intermediaries to prospectively screen employers and improve placement quality.